Workshop of bar soap making from waste cooking oil to the students guardian of learning class sabumi muslim homeschooling community in Sariwangi, West Bandung Regency - Myra Wardati Sari; Cengristitama; Pendi Riswandi; Dian Puspitasari (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2022)
Community service in the form of a workshop on making solid soap from used cooking oil with the Sabumi Homeschooling Community aimed to utilize used cooking oil waste and reduce pollution caused by household waste, provide knowledge to the community about making solid soap, and open up entrepreneurial opportunities for the community. In general, the guardians of the Sabumi Homeschooling community and their students with raw materials derived from unused materials/daily household waste. The methods used the form trials of making soap from used cooking oil, counselling about waste cooking oil and making soap theoretically, demonstrations of making solid soap from used cooking oil raw materials, and a hands-on workshop on making solid soap from a mixture of palm oil and coconut oil raw materials, as well as assistance, reports and consultations on solid soap printing results. This activity produces solid soap made from used cooking oil (pH 12), as well as solid soaps made from a mixture of palm oil and coconut oil. During the mentoring period, all participants were able to identify the process of curing solid soap, and there were 2 participants who duplicated the process of making solid soap at home with their children